2001
DOI: 10.1002/j.1939-4640.2001.tb03438.x
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Exposure to Dexamethasone Alters Leydig Cell Steroidogenic Capacity in Immature and Adult Rats

Abstract: This study examines the effects of prenatal exposure to dexamethasone (DEX) on postnatal testosterone production in male rats. Pregnant female rats were treated on gestation days 14-19 with DEX (100 microg/kg body weight per day; n = 9) or vehicle (n = 9). Results show that 35-day-old male offspring from DEX-treated pregnant females (n = 42) had decreased levels of serum testosterone (45.6% lower, P < .05) compared with control offspring (n = 43), although serum luteinizing hormone (LH) levels were not signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
30
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 60 publications
5
30
0
Order By: Relevance
“…Furthermore, a recent study showed that DEX exposure during the last week of gestation significantly increases hippocampal 11␤-HSD-1 mRNA and protein expression in newborn rat offspring compared with controls (54). Because DEX administration to pregnant dams results in a precipitous decrease in maternal levels of serum CORT (10,36), the adult offspring in our study were effectively exposed to a unique in utero environment of low maternal CORT and 11␤-HSD-1; C) mRNA expression in hippocampal tissues from control and DEX-exposed rats under both unrestrained and restraint-stressed conditions as determined by real-time PCR analysis. Values are expressed in relative units, with the group expressing the lowest level of GR, MR, or 11␤-HSD-1 being set to 1.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a recent study showed that DEX exposure during the last week of gestation significantly increases hippocampal 11␤-HSD-1 mRNA and protein expression in newborn rat offspring compared with controls (54). Because DEX administration to pregnant dams results in a precipitous decrease in maternal levels of serum CORT (10,36), the adult offspring in our study were effectively exposed to a unique in utero environment of low maternal CORT and 11␤-HSD-1; C) mRNA expression in hippocampal tissues from control and DEX-exposed rats under both unrestrained and restraint-stressed conditions as determined by real-time PCR analysis. Values are expressed in relative units, with the group expressing the lowest level of GR, MR, or 11␤-HSD-1 being set to 1.…”
Section: Discussionmentioning
confidence: 99%
“…This implies that stress or malnutrition (which attenuate the placental 11␤-HSD2 barrier to maternal glucocorticoids) in pregnancy may reveal TDS spectrum disorders in human populations exposed to numerous chemicals with antiandrogenic activity (32,33). How glucocorticoids amplify antiandrogenic effects in the fetal testis/reproductive tract remains to be determined, but fetal glucocorticoid exposure alters proliferation and function of the adult Leydig cell population (55,56), perhaps by down-regulating steroidogenic enzyme expression (57), key nodes in the effects of androgens on testicular development (58). Although recent reviews have suggested that there is an urgent need to consider the toxicological effects of pharmaceutical agents and endocrine-disrupting chemicals on the hypothalamic-pituitary-adrenal axis (17,59), this is the first study to report that interactions between glucocorticoids and environmental chemicals known to have an effect on reproductive development may play a causative role in increasing disease susceptibility.…”
mentioning
confidence: 97%
“…These data document the programming effect of Dx at the level of the pituitary gland. A clear programming effect of Dx was also detected at the level of the hypothalamus [Lim et al, 2014] and gonads [Page et al, 2001;Ristić et al, 2008;Poulain et al, 2012]. These changes at all three levels of the hypothalamo-pituitary-gonadal axis undoubtedly contribute to the impaired reproductive function during adulthood.…”
Section: Discussionmentioning
confidence: 86%
“…Lim et al [2014] suggest that glucocorticoid overexposure during late gestation affects the total number and dendritic development of gonadotropin-releasing hormone neurons in postnatal male rats. Prenatal exposure to Dx was found to decrease testosterone levels and testosterone production by isolated Leydig cells in offspring [Page et al, 2001]. Maternal betamethasone administration in sheep reduced the length of testicular cords, the amount of interstitial tissue and testicular weight [Pedrana et al, 2008].…”
Section: Effects Of Prenatal Dexamethasone On the Rat Pituitary Glandmentioning
confidence: 99%